Landscape response to Pleistocene-Holocene precipitation change in the Western Cordillera, Peru: 10Be concentrations in modern sediments and terrace fills - McPhillips,D; Bierman,PR; Crocker,T; Rood,DH (Journal of Geophysical Research: Earth Surface, 2013)
The landscape response to climate change is frequently investigated with models because natural experiments on geologic timescales are rare. In Quebrada Veladera, in the western Andes Mountains, the formation of alluvial terraces during periods of high precipitation presents opportunities for such an experiment. We compare drainage-average erosion rates during Pleistocene terrace deposition with Holocene rates, using cosmogenic 10Be samples for seven pairs of quartz sand taken from the trunk and tributaries of Quebrada Veladera and adjacent terraces. Each pair consists of sediment collected from the modern channel and excavated from an adjacent fill terrace. The terrace fill was deposited at ~16 ka and preserved an isotopic record of paleoerosion rates in the Late Pleistocene. Modern sands yield 10Be concentrations between 1.68 × 105 and 2.28 × 105 atoms/g, corresponding to Holocene erosion rates between 43 ± 3 and 58 ± 4 mm/kyr. The 10Be concentrations in terrace sands range from 9.46 × 104 to 3.73 × 105 atoms/g, corresponding to paleoerosion rates from 27 ± 2 to 103 ± 8 mm/kyr. Smaller, upstream tributaries show a substantial decline in erosion rate following the transition from a wet to dry climate, but larger drainage areas show no change. We interpret this trend to indicate that the wetter climate drove landscape dissection, which ceased with the return to dry conditions. As channel heads propagated upslope, erosion accelerated in low-order drainages before higher-order ones. This contrast disappeared when the drainage network ceased to expand; at that point, erosion rates became spatially uniform, consistent with the uniformity of modern hillslope gradients. Key Points Landscape response to climate change evaluated with 10Be erosion rates Wetter climate associated with rapid erosion in smaller, upstream drainages Drier, Holocene climate associated with spatially uniform erosion rates ©2013. American Geop